Rapid manufacturing and rapid tooling of polymer miniaturized parts using Stereolithography - Salmoria,Gean Vitor (2008)
Currently, miniaturization is a major trend in the manufacturing and commercialization of new industrial products. When small-sized objects should be manufactured with dimensions of only a few millimeters or less, many difficulties can appear using traditional processes. An alternative to study these new requirements is through the use of rapid prototyping technologies. Stereolithography (SL) has established itself as one of the most popular and reliable process allowing the rapid manufacturing of complex parts. This paper investigates the SL process, which directly produces small parts by rapid manufacturing, and also indirectly by rapid tooling. The processability of small parts was investigated using two different shapes. The POM and ABS materials were used in the indirect manufacturing. The dimensional accuracy, precision and tolerance of micro parts were evaluated using metrological techniques. Results showed accuracy and precision greater than 97% when small-parts are manufactured directly by Stereolithography.